Kesiapsiagaan puskesmas dalam menghadapi perubahan iklim yang berdampak pada kesehatan: A systematic review - Susanti, Epi; Yetti, Krisna; Pujasari, Hening; Gayatri, Dewi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Climate change has the potential to significantly impact public health. Primary health facilities must be prepared to provide effective health services to address the health impacts of climate change. Purpose: To determine the preparedness of community health centers in facing climate change that has an impact on health. Method: The approach used is Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA). The search format using Patient, Intervention, Comparison, Outcome (PICO) was formulated to facilitate the process of searching literature from databases. The databases used are ScienceDirect, Sage Journal and Scopus from 2020-2024. Researchers use the Mendeley application to detect duplication. Results: The final search results obtained 10 articles, from these articles were obtained preparedness efforts that can be carried out by health centers through routine training, building knowledge, attitudes, and practices of health workers, and building positive perceptions about preparedness. Health centers can respond to the impacts of climate change more effectively with the support of a structured framework. Conclusion: Increasingly extreme climate change has a significant impact on public health, thus requiring better preparedness from health facilities such as community health centers. Keywords: Climate Change; Health Centers; Preparedness. Pendahuluan: Perubahan iklim berpotensi m.emberi dampak besar bagi kesehatan masyarakat. Fasilitas kesehatan primer dituntut memiliki kesiapsiagaan untuk memberi pelayanan kesehatan yang efektif dalam merespon dampak kesehatan akibat perubahan iklim. Tujuan: Untuk mengetahui kesiapsiagaan puskesmas dalam menghadapi perubahan iklim yang berdampak pada kesehatan. Metode: Pendekatan yang digunakan adalah Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA). Format pencarian dengan menggunakan Patient, Intervention, Comparison, Outcome (PICO) dirumuskan untuk memudahkan dalam proses pencarian literatur dari database. Database yang digunakan adalah ScienceDirect, Sage Journal dan Scopus dari tahun 2020-2024. Peneliti menggunakan aplikasi Mendeley untuk mendeteksi Duplikasi. Hasil: Hasil akhir pencarian didapatkan 10 artikel, dari artikel tersebut didapatkan upaya kesiapsiagaan yang dapat dilakukan oleh puskesmas melalui pelatihan rutin, membangun pengetahuan, sikap, dan praktik tenaga kesehatan, serta membangun persepsi positif tentang kesiapsiagaan. Puskesmas dapat merespons dampak perubahan iklim secara lebih efektif dengan dukungan kerangka kerja yang terstruktur. Simpulan: Perubahan iklim yang semakin ekstrem menimbulkan dampak signifikan terhadap kesehatan masyarakat, sehingga menuntut kesiapsiagaan yang lebih baik dari fasilitas kesehatan seperti puskesmas. Kata Kunci: Kesiapsiagaan; Perubahan Iklim; Puskesmas.